How can FinTech achieve sustainable finance goals? A Systematic Literature Review - Nila Sari, Pratiwi; Tumiur Mauli Carolin Simorangkir, Rona (Dinasti Publisher, 2025)
The research question (RQ) in this article is “How can FinTech achieve sustainable finance goals”. According to RQ, we try to identify it through a systematic literature review. We identified articles related to fintech and sustainable finance published between 2019 to 2022. A systematic review is a type of research methodology that seeks to assess, locate, and examine all prior findings that are pertinent to a specific topic, research question, or emerging phenomenon. The review was conducted using a systematic review approach with PRISMA criteria, based on a thorough examination of pertinent literature (research articles, policy documents, and reports). Fintech & sustainable finance is the article least discussed by publishers, this is interesting because there is still minimal exploration of this issue. The articles that discuss fintech and sustainable finances from 2019 until 2022 only have 1 article namely 2020. From the results of the literature review that has been carried out,it can be seen that research journals discussing fintech and sustainable finance are still very rare, so it can be recommended that future researchers take research topics on fintech and sustainable finance.